2016
DOI: 10.1002/anie.201606113
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Primary Amide for the Selective Recovery of Gold from Secondary Resources

Abstract: Waste electrical and electronic equipment (WEEE) such as mobile phones contain a plethora of metals of which gold is by far the most valuable. Here we describe a simple primary amide that achieves the selective separation of gold from a mixture of metals typically found in a mobile phone by extraction into toluene from an aqueous HCl solution; unlike current processes, reverse phase transfer is achieved simply using water. Phase transfer occurs by dynamic assembly of protonated and neutral amides with AuCl4 − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(91 citation statements)
references
References 28 publications
4
87
0
Order By: Relevance
“…[15][16][21][22] Yet comparable work on heavier elements, including the platinum group metals (PGMs), lanthanides, and actinides, are scarce. 23 This is despite the fact that many modern lighting, displays, and carbon-free energy technologies rely on the efficient refining and reprocessing of heavy metals based upon liquid:liquid extraction (LLE) technologies; 1,24 most of these processes involve the interaction of aqueous interfaces with the anionic complexes of heavy elements in highly concentrated solutions. [24][25][26] In addition to its practical implications, a molecular scale understanding of interfacial water in the presence of large ions is the best way to test the limits of the theories that explain specific-ion effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][21][22] Yet comparable work on heavier elements, including the platinum group metals (PGMs), lanthanides, and actinides, are scarce. 23 This is despite the fact that many modern lighting, displays, and carbon-free energy technologies rely on the efficient refining and reprocessing of heavy metals based upon liquid:liquid extraction (LLE) technologies; 1,24 most of these processes involve the interaction of aqueous interfaces with the anionic complexes of heavy elements in highly concentrated solutions. [24][25][26] In addition to its practical implications, a molecular scale understanding of interfacial water in the presence of large ions is the best way to test the limits of the theories that explain specific-ion effects.…”
Section: Introductionmentioning
confidence: 99%
“…23 This is despite the fact that many modern lighting, displays, and carbon-free energy technologies rely on the efficient refining and reprocessing of heavy metals based upon liquid:liquid extraction (LLE) technologies; 1,24 most of these processes involve the interaction of aqueous interfaces with the anionic complexes of heavy elements in highly concentrated solutions. [24][25][26] In addition to its practical implications, a molecular scale understanding of interfacial water in the presence of large ions is the best way to test the limits of the theories that explain specific-ion effects. It is known that the thermochemical radii of ions plays an important role in their interfacial interactions, 23 and a recent study demonstrated qualitative differences in the adsorption behavior of heavy and light anions at a charged interface.…”
Section: Introductionmentioning
confidence: 99%
“…This valuable material is extracted from ores with a low abundance of gold. Recently, waste electrical and electronic equipment (WEEE) has been recognized as an attractive source of gold, because the gold content of WEEE is estimated to be 80 times higher than that found in global primary gold mining deposits . To extract the limited amount of gold from ores or WEEE, the following steps are necessary: 1) oxidative leaching of gold from solid ore or WEEE, 2) separation and concentration of gold ions from the leaching solution and 3) reduction of extracted gold ions to neutral gold materials.…”
Section: Methodsmentioning
confidence: 99%
“…This precious metal plays important roles in jewellery, modern electronics, medicine, chemical catalysis and in national economy because of its high usage and wide applications. [1][2][3][4][5] So the demand for gold is rapidly increasing day by day. In nature, gold exists in various oxidation states such as 0, +1, and +3.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many methods were used to recover gold from ores and WEEE. 5,[13][14][15][16][17][18] However, highly selective sensing and extraction of Au 3+ is always a signicant challenge because other metal ions such as ferric, aluminium, magnesium, nickel, copper and zinc ions etc. are coexist with gold ion in the waste streams.…”
Section: Introductionmentioning
confidence: 99%